Mantle influx compensates crustal thinning beneath the Cathaysia Block, South China: Evidence from SINOPROBE reflection profiling - Dong, Shuwen; Li, Jianhua; Cawood, Peter A.; Gao, Rui; Zhang, Yueqiao; Xin, Yujia (Earth and planetary science letters, 2020)
•A deep seismic profile reveals the crustal architecture of SE South China.•Coastal crust shows a magma-dominated architecture related to Cretaceous extension.•We show seismic records of magmatic underplating that compensates for crustal thinning.•Magmatic underplating was responsible for Cretaceous generation of a flat Moho.•Magma-compensating formed an integral part of crustal growth of East Cathaysia. The crustal architecture of the Cathaysia Block, South China, is a key element in understanding the late Mesozoic tectono-magmatic history of East Asia, and includes a spectacular (∼260,000 km2) basin and igneous province that forms a natural laboratory for unravelling the interplay of extension, magmatism and crust-mantle interaction. Here we analyze the whole crustal architecture of East Cathaysia through a ∼300-km-long SINOPROBE deep seismic reflection profile. This profile reveals that East Cathaysia is underlain by two seismically distinct terranes (i.e., the Wuyishan and Coastal terranes), separated by a low-angle, northwest-dipping set of mantle-penetrating reflectors interpreted as the Zhenghe-Dapu fault zone, which documents Neoproterozoic terrane amalgamation and Cretaceous extensional reactivation. The seismic image of the Coastal terrane shows large-scale low reflectivity truncated by arrays of high-reflective subhorizontal bands of layered reflectors, corresponding to an extension-related crustal architecture dominated by extensive Cretaceous magmatism. The layered reflectors are interpreted to represent mantle-derived mafic sills, which document significant magmatic underplating associated with asthenospheric upwelling beneath the terrane. This interpretation accounts for the localized distribution of Cretaceous magmatic rocks in the Coastal terrane. We suggest that the magmatic underplating added large volumes of mantle-derived material to the crust, compensating for the crustal thinning. Such a magma-compensating process might have formed an integral part of crustal reworking and growth in creating the magma-dominated crust and the broadly flat Moho of the Coastal terrane during the Cretaceous.